Dielectric and Relaxor Ferroelectric Properties in \(\text{PZT-PMnN-PSbN}\) Ceramics - Huy, Than Trong; Luan, Nguyen Dinh Tung; Chuong, Truong Van; Hong, Le Van (Communications in Physics, 2012)
The rhombohedral perovskite 0.9Pb(Zr0.5Ti0.5)O3 – xPb(Mn1/3Nb1/3)O3 – (0.1-x)Pb(Sb1/2Nb1/2)O3, x = 0.05; 0.06; 0.07; 0.08; 0.09; 0.1 (PZT – PMnN – PSbN) ceramic was synthesized by the Columbite precursor rout. The temperature dependence of dielectric constant and its loss in a frequency region of 0.1 kHz – 500 kHz were measured in aim to search the weak-field dielectric response in PZT-PMnN-PSbN systems. A high value of εmax > 20000 was found at 1 kHz with the temperature Tm of around 575K. Using an extended Curie-Weis law the diffuse phase transition was determined. Fitting by using Vogel – Fulcher and power relationship indicated that the polarization fluctuation above the static freezing temperature behaves like as a spin-glass one. Cole – Cole analyses showed the non – Debye type relaxation in the system